Problems of surface water protection in the context of land relations in the South of Russia - Yu. B. Babina; B. I. Kochurov (Юг России: экология, развитие, 2021)
Aim. The aim was to analyse the use and protection of land surface water bodies in the context of land relations based on theoretical concepts of the inseparability of water bodies and the land occupied by them. Material and Methods. An integrated approach based on a combination of statistical methods and a comparative legal method were used to analyse and compare dynamic and territorial series of cadastral accounting data and cadastral maps.Results. The existing problems in the formation of lands of the Water Fund are caused primarily by inconsistency in maintaining the water register. Therefore, large areas under water bodies are not included in the land of the water Fund and are not protected from arbitrary use. This is fraught with potential harm to water bodies including their complete destruction. Such discrepancies are most typical for most regions within the North Caucasus Federal District.Conclusion. Analysis showed that the actual status of the majority of water bodies in the territory is quite irregular and that there are widespread inconsistencies with the norms stipulated by the legislation in relation to land under water in the independent category of "land of the Water Fund". In practice, the composition of this category is formed independently of the established criteria for such selection. These inconsistencies are due to the inconsistency of the norms themselves regarding the formation of water Fund lands and the disinterest of land users and local authorities in transferring land under surface water bodies to the category of water Fund lands due to restrictions imposed by legislation on their use.